2010
DOI: 10.1177/1094670510369378
|View full text |Cite
|
Sign up to set email alerts
|

Customer and Frontline Employee Influence on New Service Development Performance

Abstract: Service firms recognize the key role that product and process innovation play in building and sustaining competitive advantage in the marketplace. This empirical study tests a model of new service development (NSD) that enhances performance outcomes by prescribing specific roles for customers and frontline employees in the NSD process. Findings are based on in-depth managerial interviews and survey data collected from 160 organizations across a variety of service sectors. The results support hypotheses that cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
3
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 30 publications
10
175
3
3
Order By: Relevance
“…Babakus, Yavas, Karatepe and Avci (2003) analyzed the essential attributes of the growth of the financial performance of the commercial bank, and stated that the area of job satisfaction is an important factor that significantly affects ability of staff to provide quality data to their clients. Similar conclusions are indicated also by Matzler and Renzl (2006), Melton andHartline (2010), or Saura, Contrí, Taulet andVelasquez (2005). Yee, Yeung and Cheng (2010) indicate that loyal employees have many opportunities to understand and meet specific needs of bank customers, which represents a higher quality of services.…”
Section: Basic Attributes Of Employee Satisfaction In the Banking Sectorsupporting
confidence: 69%
“…Babakus, Yavas, Karatepe and Avci (2003) analyzed the essential attributes of the growth of the financial performance of the commercial bank, and stated that the area of job satisfaction is an important factor that significantly affects ability of staff to provide quality data to their clients. Similar conclusions are indicated also by Matzler and Renzl (2006), Melton andHartline (2010), or Saura, Contrí, Taulet andVelasquez (2005). Yee, Yeung and Cheng (2010) indicate that loyal employees have many opportunities to understand and meet specific needs of bank customers, which represents a higher quality of services.…”
Section: Basic Attributes Of Employee Satisfaction In the Banking Sectorsupporting
confidence: 69%
“…For example, Den Hertog (2000) introduces the term 'client-interface innovations' and maintains that "the way the service provider interacts with the client can itself be a source of innovation" [Den Hertog, (2000), p.496]. This is in line with the service innovation literature, which suggests that firms involve customers in the idea generation phase and to a lesser extent in later phases of the new service development process (e.g., Carbonell et al, 2012;Melton and Hartline, 2010). Finally, over time, the provider assimilates complementing goods-related knowledge from interactions with the customer (Foss et al, 2011).…”
Section: Conceptual Backgroundsupporting
confidence: 64%
“…Since previous S-D logic innovation research has shown that personnel external to the R&D department, e.g. managers and frontline employees, contribute to firms' creation of value propositions (Cadwaller et al 2010;Melton and Hartline 2010;Ordanini and Parasuraman 2011), we focused on innovation projects comprised of such personnel.…”
Section: Methods Data Collectionmentioning
confidence: 99%